Motivation Analysis Learning in The Implementation of Physics Practicum - Muhammad Syahrul Kahar (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
Physics learning aims to gain an understanding of facts, the ability to recognize and solve problems on an object, and have a scientific attitude that can be demonstrated in everyday reality. With the development of curriculum in universities, students are allowed to further hone their skills in following the learning in the classroom. The method used in this research is quantitative approach by using questionnaire of learning motivation, learning result as a data source. The population at the same time the subject used is Civil Engineering student class A with total 35 students. The results showed that the average student learning outcomes were 74, 65, the standard deviation of 5.37 with the highest score was in the score of 85.00 and the lowest score was 66.00, the learning motivation scores were in the 100-130 interval for the high category, score 0 -80 medium category. Regression test results obtained tcount: 7, 54> ttable: 1.68, with a significance level of 0.05. So the motivation to learn students in the implementation of lab laboratory is very supportive students in construct knowledge and skills possessed. The conclusion in this research is the need of improvement from the aspect of student's learning motivation in following the learning or the implementation of practicum activities so that the learning outcomes obtained are satisfactory.